Formulasi dan Penentuan Nilai SPF (Sun Protection Factor) Sediaan Gel Ekstrak Bunga Krisan (Chrysanthemum indicum L.) - Wintariani, Ni Putu; Suryaningsih , Ni Putu Aryati; Ardinata, I Putu Riska; Wartana, I Gusti Ngurah Agung Windra (Jurnal Ilmiah Medicamento, 2025)
Exposure to ultraviolet (UV) radiation can lead to various forms of skin damage, necessitating effective protective measures. One commonly employed approach is the use of sunscreen formulations capable of absorbing or reflecting UV rays before they penetrate deeper layers of the skin. The extract of Chrysanthemum indicum L. flowers contains bioactive compounds such as flavonoids, tannins, and alkaloids, which exhibit potential as natural sunscreen agents. This study aimed to formulate a gel-based sunscreen containing Chrysanthemum indicum flower extract and to evaluate its Sun Protection Factor (SPF) and physicochemical characteristics. The formulations were prepared with three extract concentrations: F1 (5%), F2 (10%), and F3 (20%), using a gel base composed of Carbopol 940 (0.5%), triethanolamine (0.5%), glycerin (10%), methylparaben (0.2%), and purified water. Physical evaluations included pH, viscosity, and spreadability tests. The results showed that all formulations met the standard criteria for gel preparations, with pH values ranging from 4.25 to 4.66, viscosities from 22.70 to 38.46 Pa·s, and spreadability between 5.04 and 5.21 cm. SPF values were determined in vitro using UV-Vis spectrophotometry (290-400 nm), revealing an increase in SPF with higher extract concentrations: negative control (1.395), F1 (1.795), F2 (2.506), and F3 (5.041). These findings suggest that Chrysanthemum indicum flower extract holds promise as a safe and environmentally friendly active ingredient for natural sunscreen development.